Strategies and Forms of Communication Writing The Novel "Cold Baby” By Witzlu on The Online Novel Digital Platform - Sriningsih Sriningsih (Journal of Social Science, 2023)
This research explores the strategies and forms of communication employed in the creation of the novel "Cold Baby" by Witzlu on the online digital novel platform. Language plays a crucial role in human communication, and the written language is a significant medium for conveying ideas and information. Writing skills, particularly in literature, are essential but often lack adequate publication and promotional strategies, hindering the writer's impact. Effective novel writing strategies encompass understanding the target audience, selecting a unique genre, choosing a compelling plot, crafting strong characters, creating engaging conflicts, using narrative techniques, employing dialogue effectively, and varying language styles. In the digital age, writers have embraced online platforms for publishing and promoting their works, reaching a wide readership and contributing to the growth of Indonesian literature in digital form. The research aims to shed light on these strategies, inspiring aspiring writers to create quality digital literature and enrich Indonesia's literary heritage.